Circumventing Antivector Immunity by Using Adenovirus-Infected Blood Cells for Repeated Application of Adenovirus-Vectored Vaccines: Proof of Concept in Rhesus Macaques - Sun, Caijun (American Society for Microbiology, 2012)
Adenovirus has been extensively exploited as a vector platform for delivering vaccines. However, preexisting antiadenovirus immunity is the major stumbling block for application of adenovirus-vectored vaccines. In this study, we found that freshly isolated peripheral blood mononuclear cells (PBMCs), mostly CD14(+) cells, from adenovirus serotype 5 (Ad5)-seropositive primates (humans and rhesus macaques) can be efficiently infected with Ad5 in vitro. On the basis of this observation, a novel strategy based on adenoviral vector-infected PBMC (AVIP) immunization was explored to circumvent antivector immunity. Autologous infusion of Ad5-SIVgag-infected PBMCs elicited a strong Gag-specific cellular immune response but induced weaker Ad5-neutralizing antibody (NAb) in Ad5-seronegative macaques than in macaques intramuscularly injected with Ad5-SIVgag. Moreover, Ad5-seropositive macaques receiving multiple AVIP immunizations with Ad5-SIVenv, Ad5-SIVgag, and Ad5-SIVpol vaccines elicited escalated Env-, Gag-, and Pol-specific immune responses after each immunization that were significantly greater than those in macaques intramuscularly injected with these Ad5-SIV vaccines. After challenged intravenously with a highly pathogenic SIVmac239 virus, macaques receiving AVIP immunization demonstrated a significant reduction in viral load at both the peak time and set-point period compared with macaques without Ad5-SIV vaccines. Our study warranted further research and development of the AVIP immunization as a platform for repeated applications of adenovirus-vectored vaccines.